The PATRIARCH Study. Using outcome measures for league tables: Can a North American prediction of admission score be used in a United Kingdom children's emergency department?. Issue 6 (1st November 2002) - Miles, H; Litton, E; Curran, A; Goldsworthy, L; Sharples, P; Henderson, A J
Abstract : Objectives: The use of league tables has become predominant in the healthcare culture of the United Kingdom. These tables are often based on measures that are viewed with scepticism by clinicians. This study was designed to test the validity of a North American risk of admission score, the PRISA, for use in a United Kingdom population of accident and emergency (A&E) attendees. Methods: All attendees to a children's A&E department were scored using the PRISA for a single calendar month (November 2000) Results: 701 children were studied in total. The results show that the PRISA applied to this population gives an area under the receiver operator curve of 0.76. Of the 701 patients studied, 206 (29.4%) were admitted. The PRISA predicted a total of 206.10 admissions. Of the 50 patients discharged with the highest PRISA scores (that is, with the highest likelihood of admission), none were admitted in the 48 hours after their original attendance. Conclusions: These results show that the PRISA is suitable as a measure of paediatric A&E department performance in the United Kingdom and it is highly promising as a future measure of quality.